If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = 4x + -1 Reorder the terms: -3 + 3x = 4x + -1 Reorder the terms: -3 + 3x = -1 + 4x Solving -3 + 3x = -1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 3x + -4x = -1 + 4x + -4x Combine like terms: 3x + -4x = -1x -3 + -1x = -1 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + -1x = -1 + 0 -3 + -1x = -1 Add '3' to each side of the equation. -3 + 3 + -1x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -1 + 3 -1x = -1 + 3 Combine like terms: -1 + 3 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 2x+28=10x-44 | | 5-2y=7 | | 6x+6=-144-9x | | 11x+5=6x+25 | | 3(2x+4)=48 | | -6=-3t^2+9t-.75 | | -6=-3t^2+9t-.075 | | x^2-8x=-10 | | 6e-7=21.8 | | x+3x=22 | | 7x+3=2(3x-2)+7 | | 2x-5=1/4+5x | | 7x^2-20x+12=0 | | 7x+3=2(3x-2)+8 | | 3x^3-3x^2+4x-4=0 | | -7(4x-8)=-28x+64 | | x^2-12x=-20 | | x^2-2=7 | | 8(2x-8)=2(8x+5) | | 6ac-3ad+8bc-4bd=0 | | 9+4x=42+x | | 5(2x-6)=10(x-3) | | x^6-2x^3-8=0 | | 10k+4=40 | | 4x=3(x+33) | | 4x-4=96 | | 5x+8=5(x-2) | | 7m-4=31 | | 3(3x+1)+5(x-2)= | | 15r^2-70r-245=0 | | 108-5x=31x+16 | | 3x^2+10=4x |